Views of commissioners, managers and healthcare professionals on the NHS Health Check programme: a systematic review. Issue 11 (15th November 2017) - Mills, Katie; Harte, Emma; Martin, Adam; MacLure, Calum; Griffin, Simon J; Mant, Jonathan; Meads, Catherine; Saunders, Catherine L; Walter, Fiona M; Usher-Smith, Juliet A
Abstract : Objective: To synthesise data concerning the views of commissioners, managers and healthcare professionals towards the National Health Service (NHS) Health Check programme in general and the challenges faced when implementing it in practice. Design: A systematic review of surveys and interview studies with a descriptive analysis of quantitative data and thematic synthesis of qualitative data. Data sources: An electronic literature search of MEDLINE, Embase, Health Management Information Consortium, Cumulative Index of Nursing and Allied Health Literature, Global Health, PsycInfo, Web of Science, OpenGrey, the Cochrane Library, NHS Evidence, Google Scholar, Google, ClinicalTrials.gov and the International Standard Randomised Controlled Trial Number registry from 1 January 1996 to 9 November 2016 with no language restriction and manual screening of reference lists of all included papers. Inclusion criteria: Primary research reporting views of commissioners, managers or healthcare professionals on the NHS Health Check programme and its implementation in practice. Results: Of 18 524 citations, 15 articles met the inclusion criteria. There was evidence from both quantitative and qualitative studies that some commissioners and general practice (GP) healthcare professionals were enthusiastic about the programme, whereas others raised concerns around inequality of uptake, the evidence base and cost-effectiveness. In contrast, those working in pharmacies were all positive about programme benefits, citing opportunities for their business and staff. The main challenges to implementation were: difficulties with information technology and computer software, resistance to the programme from some GPs, the impact on workload and staffing, funding and training needs. Inadequate privacy was also a challenge in pharmacy and community settings, along with difficulty recruiting people eligible for Health Checks and poor public access to some venues. Conclusions: The success of the NHS Health Check Programme relies on engagement by those responsible for its commissioning, management and delivery. Recognising and addressing the challenges identified in this review, in particular the concerns of GPs, are important for the future of the programme.